Endogean and cavernicolous Coleoptera of the Balkans. XV. A new species of the genus Ioniorhynchus Magrini, Meoli & Abbazzi, 2005 (Coleoptera: Curculionidae: Entiminae) from Greece - Hlaváč, Peter; Skuhrovec, Jiří (Zootaxa, 2016)
Ioniorhynchus henderickxi sp. nov. is described and illustrated from Zakynthos, Spilia Cagioti-Giri, Greece. The new species is compared closely with the sympatric I. doriae A. & F. Solari 1904. The taxonomic status of the genus is discussed, and an annotated catalogue of all anopthalmous species of the tribe Otiorhynchini of Balkan Peninsula is provided.
Keywords: Body Size; velikost orgánu; Animals; Organ Size; Řecko; Greece; mužské pohlaví; Male; rozšíření zvířat; velikost těla; Weevils; zvířata; Animal Distribution; nosatcovití